PENGARUH TEKNIK KONTRAK PERILAKU UNTUK MENGURANGI PERILAKU KECANDUAN BERMAIN GAME ONLINE PADA SISWA DI SMPN 13 PEKANBARU - Maulana, Khairul; Yakub, Elni; Mardes, Siska (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract:This study aims to examine the effects of contingency contracting techniques in reducing the , addictive behavior playing online games of students in SMPN 13 Pekanbaru. The quantitative research method was used in this study and the research was designed based on the one-group pretest – posttest design. The measuring instrument used in this study was the aggressive behavioural measurement scale consisting of 50 and 44 items before and after validation respectively. The validity score was calculated to be 0.25 and the reliability score was obtained as 0.949. The subject was determined by using purposive sampling technique, and it was obtained that 7 students in SMPN 13 Pekanbaru were identified as having a high level of addictive behavior playing online games. The data were analysed by using the non-parametric statistical technique and were tested by using the Wilcoxon analysis test. This is known from